2012
DOI: 10.1007/s00787-012-0305-6
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine pharmacogenetics in child and adult populations

Abstract: Although fluoxetine is useful in the treatment of major depression, 30-40 % of the patients do not respond to therapy. The response seems to be influenced by certain genes which are involved in the drug's pharmacodynamics and pharmacokinetics. The present study reviews the literature on genetic contributions to fluoxetine response in children and adults, and concludes that the different polymorphisms of CYP2D6 and CYP2C9 may influence the blood concentrations of fluoxetine. If the childhood dose is adjusted fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 77 publications
1
17
0
2
Order By: Relevance
“…Pharmacogenetic approaches are particularly relevant in pediatric populations due to several reasons: first, most studies of the pharmacodynamics of ADs have been conducted in adults, making studies of the pharmacogenetics of SSRI in children scarce (Blazquez et al 2012). Second, pharmacogenetic approaches are particularly relevant in pediatric populations because of concerns about the suicide risk of SSRIs, resulting in a black-box warning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacogenetic approaches are particularly relevant in pediatric populations due to several reasons: first, most studies of the pharmacodynamics of ADs have been conducted in adults, making studies of the pharmacogenetics of SSRI in children scarce (Blazquez et al 2012). Second, pharmacogenetic approaches are particularly relevant in pediatric populations because of concerns about the suicide risk of SSRIs, resulting in a black-box warning.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date there is no robust and consistent evidence implicating any specific candidate gene or polymorphism that is associated with AD response or side effect (SE) profile in pediatric population (Blazquez et al 2012;Murphy et al 2003). Preliminary pharmacogenetic research has suggested an important role for genes related to serotonin function in AD SEs (Kato and Serretti 2010;Murphy et al 2003;Serretti and Artioli 2004).…”
Section: Introductionmentioning
confidence: 99%
“…To date, a large number of gene mutations associated with chemosensitivity and cytotoxicity have been found. For example, ERCC1 gene mutations confer resistance to platinum [17], and CYP2C9 mutations reduce sensitivity to ifosfamide [18]. However, additional therapeutic targets that will potentially benefit osteosarcoma patients need to be identified.…”
Section: Introductionmentioning
confidence: 98%
“…This scenario is even slower for child and adolescents mental disorders. In this issue of the journal, Blazquez et al [1] present an extensive review of the literature describing how certain genes are involved in the pharmacodynamics and pharmacokinetics of fluoxetine in children and adolescents. Initial exciting findings seem to suggest a potential role for polymorphisms in several genes like SLC6A4, HTR1A and MAO-A as moderators of response to fluoxetine in depression.…”
mentioning
confidence: 99%